Whipplova bolezen - Kern, Izidor (Zdravniški vestnik, 2009)
Background Whipple's disease is a chronic, multisystemic disease caused by a microorganism named Tropheryma whipplei. Disease is rare, so it presents a diagnostic problem to clinicians. Long-term treatment with antibiotics is successful. We report two patients with longstanding complaints and accurate histopathological diagnosis further on confirmed by molecular biology test. Methods Both patients presented with malaise, weight loss and laboratory parameters of chronic infection. Since rheumatological, haemathological and infective causes of complaints were ruled out, patients were admitted to our hospital. Histopathological examination in both cases confirmed Whipplećs disease and antibiotic treatment was started. Polymerase chain reaction using specific oligonucleotide primers for 16S rRNA was performed on formalin-fixed,paraffin-embedded tissue samples of both patients and peripheral blood of one patient. Results One patient presented with advanced disease and despite antibiotic treatment he died with signs of pulmonary arterial hypertension. The other patient was diagnosed early in the course of the disease and antibiotic treatment was effective. In tissue samples of both patients we found PAS-positive intracellular bacilli. By PCR method we detected a specific gene segment of Tropheryma whipplei in tissue samples and peripheral blood. Conclusions Presented two cases confirm the rarity of Whipplećs disease and illustrate the variety of nonspecific clinical findings which lead to late diagnosis. Histopathological changes are very specific on PAS staining. Molecular biology test aids in disease confirmation.
Keywords: Diagnosis; diagnostika; Etiology; infekcijske bolezni; Middle Age; Pathology; Polimerazna, verižna reakcija; Polymerase Chain Reaction; RNA ribosomska, 16S; RNA, Ribosomal, 16s; Srednja leta; therapy; vnetja; Whipplejeva bolezen; Whipple's Disease; Whipplova bolezen; zdravljenje